Instrumentality and influence of Fayol's doctrine: history, politics and emotions in two post-war settings. Issue 7 (28th September 2022) - Berber, Aykut; Harding, Nancy; Mughal, Farooq
Abstract: Why does Administration Industrielle et Générale have a major status in the history of management thought? We argue that the rational reason for the enthusiasm for Fayol's theory disguises the irrational and unconscious fears in societies for which the cool rationality of Fayol's work offered a soothing balm. We discuss this in two different but relatively similar post-war settings—France in the 1920s, which saw the first major upsurge of interest in Fayol's work, and the mid-twentieth century USA, where his work was rediscovered and attained canonical status. The reception to his work in the aftermaths of the two world wars prove particularly important in understanding how historico/politico/emotional affect influences the reception to a body of work. We suggest it is not the ideas themselves that were of prime importance, but how those ideas resonated with the historical, political and emotional context in which they were debated and taken up.